638 Effects of il-15 addition on the suppressed induction of ctl upon exposure to asbestos. (24th April 2018) - Kumagai-Takei, N; Nishimura, Y; Matsuzaki, H; Lee, S; Yoshitome, K; Otsuki, T
Abstract : Introduction: Asbestos exposure can cause malignant mesothelioma and lung cancer. However, in contrast, its effect on anti-tumour immunity remains unclear. Our previous study reported that asbestos exposure suppressed the induction of CTL during mixed lymphocyte reactions (MLR), accompanied by the decrease in proliferation of CD8 + T cells. Recently, we reported that IL-2 showed a tendency to increase% granzyme B + cells in the CFSE-positive CD8 + lymphocytes without proliferation upon exposure to asbestos. Therefore, we investigated whether IL-15 addition might improve the suppressed induction of CTL upon exposure to asbestos. Methods: For MLR, human PBMCs were cultured with irradiated allogenic PBMCs upon exposure to chrysotile B asbestos at 5 μg/ml for 7 days. After 2 days of culture, IL-15 was added at 1 ng/ml. After 7 days of MLR, PBMCs were collected and analysed for phenotypic and functional markers of CD8 + T cells with fluorescence-labelled anti-CD3, anti-CD8, anti-CD45RA, anti-CD45RO, and anti-granzyme B Abs using flow cytometry. Result: IL-15 didn't recover the asbestos-caused decreases in% CD25 + and% CD45RO + cells and increase in% CD45RA + cells, but recovered the decrease in cell numbers of CD3 + CD8 + cells and% granzyme B + cells, in contrast to IL-2. Discussion: These results indicate that IL-15 is more effective on recovery from asbestos-caused suppressed induction of CTL than IL-2, although the interfered expressions of cell surface markers were not recovered even by addition of IL-15. Further study about the characteristics of CD3 + CD8 + granzyme B + cells induced by addition of IL-15 will contribute to clarification for the mechanism of asbestos-caused suppression in CTL induction and to finding out a clue to restore it.